Composition and application thereof, semiconductor device and manufacturing method thereof
By using a composition of resin, organometallic ester coupling agent and non-aqueous organic solvent, the problem of excessive shrinkage of patterned films in the prior art is solved, and moderate and uniform shrinkage is achieved, which satisfies high resolution rate patterning requirements.
Patent Information
- Application Number
- CN202411477213.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-22
AI Technical Summary
The crosslinking reaction between the macromolecular crosslinking agent and the surface of the patterned film in existing patterned microscopic materials causes the patterned film to shrink too much in size, which cannot meet the requirements of high-resolution patterning.
Provided is a composition including a resin, an organometallic ester coupling agent and a non-aqueous organic solvent. Through the bridging of the organometallic ester coupling agent, the chemical connection between the resin and the surface of the patterned film is realized, and the patterned film is controlled. Size shrinkage.
The moderate dimensional shrinkage of the patterned film is achieved, the probability of graphic adhesion is reduced, the uniformity of pattern size is ensured, and the requirements of high-resolution patterning are met.
Smart Images

Figure CN118994991B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of patterning technology, and in particular to a composition and application thereof, a semiconductor device and a manufacturing method thereof. Background Art
[0002] As the integration of semiconductor integrated circuits continues to increase, the requirements for the critical dimension (CD) of the chip pattern structure are also continuously reduced, the exposure wavelength used in the patterning process is getting shorter and shorter, and the cost of exposure equipment is also increasing. Without introducing new high-cost exposure equipment, achieving pattern shrinkage of patterned thin films on substrates for manufacturing integrated circuits can improve the resolution of the functional layer pattern obtained thereby and significantly reduce manufacturing costs.
[0003] Among them, graphic miniaturization materials are often used to coat the surface of patterned films, which usually contain resins and macromolecular crosslinking agents. Under heating conditions, the macromolecular crosslinking agent can crosslink and cure the resin with carboxyl groups on the surface of the patterned film, thereby increasing the film thickness and graphic sidewalls of the patterned film, and reducing the size of through holes or line gaps in the patterned film, thereby forming a finer pattern. However, the crosslinking reaction between the macromolecular crosslinking agent and the surface of the patterned film in the existing graphic miniaturization materials usually causes the size of the patterned film to shrink too much, which may cause problems such as graphic bridging under the high-resolution patterning requirements of advanced nodes. Summary of the invention
[0004] In view of this, the embodiments of the present application provide a composition and its application, a semiconductor device and its manufacturing method, wherein the composition can enable the patterned film to have an appropriate and uniform dimensional shrinkage to meet the requirements of high-resolution patterning in the field of semiconductor devices.
[0005] Specifically, the first aspect of an embodiment of the present application provides a composition for being set on the surface of a patterned film, the composition comprising a resin, a coupling agent and a non-aqueous organic solvent, wherein the coupling agent comprises an organic metal ester coupling agent, and the central metal atom of the organic metal ester coupling agent comprises one or more of titanium, zirconium, and aluminum; the structure of the resin comprises a first repeating unit and a second repeating unit, the side chain of the first repeating unit has at least one of a hydroxyl group and a carboxyl group, the second repeating unit does not contain a hydroxyl group or a carboxyl group, and the molar proportion of the first repeating unit in all repeating units of the resin is 30%-80%.
[0006] The above composition is coated on the surface of the patterned film. Under heating conditions, the bridging effect of the above organic metal ester coupling agent can be used to achieve chemical connection between the central metal atom and the resin in the composition and the specific reactive groups (such as carboxyl, hydroxyl, etc.) on the surface of the patterned film. After removing the resin and coupling agent not connected to the surface of the patterned film, the spacing distance between the patterns in the patterned film can be appropriately reduced, the probability of pattern adhesion can be reduced, and the uniformity of the pattern size can be ensured, which can meet the requirements of high-resolution patterning.
[0007] In the embodiment of the present application, the weight average molecular weight of the resin is in the range of 1000-20000. This can ensure that the resin has high solubility in the above composition, and the resin has an appropriate number of first repeating units that can be chemically bonded with the coupling agent to effectively thicken the patterned film. In some embodiments, the weight average molecular weight of the resin is in the range of 4000-10000.
[0008] In some embodiments of the present application, the organic metal ester coupling agent includes at least one of titanate, zirconate, and aluminate. Among them, the titanate includes one or more of tetraethyl titanate, tetra-n-propyl titanate, tetraisopropyl titanate, tetra-n-butyl titanate, bis(acetylacetonato) diisopropyl titanate, di(triethanolamine) diisopropyl titanate, and hexabutoxy-μ-titanium (IV) oxide; the zirconate includes one or more of tetraethyl zirconate, tetra-n-propyl titanate, tetraisopropyl zirconate, and tetra-n-butyl zirconate; the aluminate includes one or more of triethyl aluminate, triisopropyl aluminate, tributyl aluminate, tribenzyl aluminate, triacetylacetonato aluminum, bis(acetylacetonato) isopropyl aluminate, (acetylacetonato) diisopropyl aluminate, and (ethyl acetylacetonato) diisopropoxy aluminate.
[0009] In some embodiments of the present application, the coupling agent further comprises a silane having at least 3 alkoxy groups in the structure. In some possible embodiments of the present application, the organosilane comprises an orthosilicate having a chemical formula of Si(OR)4, wherein each R is independently selected from substituted or unsubstituted C 1-6 Alkyl. Such organosilanes have strong coupling ability.
[0010] In the embodiment of the present application, the mass of the coupling agent is 1%-30% of the mass of the resin. In this way, the above composition has a suitable content of coupling agent, which ensures that it can connect a certain amount of resin to the surface of the patterned film to effectively thicken the patterned film without causing material waste of the coupling agent.
[0011] In the embodiment of the present application, in the composition, the total weight ratio of the coupling agent and the resin is 0.5wt%-5wt%. This can ensure that the graphic sidewall of the patterned film coated with the composition can be effectively thickened without causing waste of the composition.
[0012] In some embodiments of the present application, the first repeating unit includes one or more of a styrene repeating unit having at least one of a hydroxyl group and a carboxyl group on the benzene ring, an acrylate repeating unit having at least one of a hydroxyl group and a carboxyl group on the side chain, and an acrylamide repeating unit having at least one of a hydroxyl group and a carboxyl group on the side chain.
[0013] In some embodiments of the present application, the second repeating unit includes one or more repeating units derived from styrene substances that do not contain hydroxyl groups and carboxyl groups, alkyl acrylates, and alkyl methacrylates.
[0014] In the embodiment of the present application, the non-aqueous organic solvent includes one or more of an alcohol solvent and an ether solvent. These non-aqueous solvents are not likely to dissolve and damage the patterned film in contact with the composition, and can make the above-mentioned resin and coupling agent dissolve well therein.
[0015] The second aspect of the embodiment of the present application provides the use of the composition as described in the first aspect of the embodiment of the present application in reducing the critical dimension of the pattern. The application can specifically be to reduce the pattern spacing of the patterned film. With the patterned film with reduced pattern spacing, a functional layer pattern with a smaller critical dimension and higher resolution can be prepared, thereby obtaining a semiconductor device with a higher degree of integration.
[0016] A third aspect of an embodiment of the present application provides a method for manufacturing a semiconductor device, comprising:
[0017] (1) Providing a substrate having a patterned film on its surface; the surface of the patterned film has at least one of a hydroxyl group and a carboxyl group;
[0018] (2) applying the composition described in the first aspect of the embodiment of the present application to the surface of the patterned film to form a film material, and heating the film material to react with the portion of the film material in contact with the patterned film;
[0019] (3) Using a cleaning solution to remove the unreacted film material, a fine patterned film with reduced pattern spacing is obtained on the substrate.
[0020] The manufacturing method of the above-mentioned semiconductor device, by adopting the above-mentioned composition of the embodiment of the present application as a pattern shrinkage material, can achieve a moderate reduction in the pattern spacing of the formed patterned film, obtain a fine pattern with a smaller critical dimension at a lower cost, and ensure that the defects of the obtained pattern are small, which is conducive to the development of ultra-high integration of semiconductor devices.
[0021] In some embodiments of the present application, after obtaining a fine patterned film with reduced pattern spacing in step (3), the method may further include: transferring the pattern of the fine patterned film to a substrate to obtain a patterned substrate. Further, after obtaining the patterned substrate, the method may further include: forming a structure required for a semiconductor device on the patterned substrate.
[0022] The embodiment of the present application also provides a semiconductor device, which is manufactured using the manufacturing method described in the third aspect of the embodiment of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 A schematic diagram showing the use of the composition of an embodiment of the present application to reduce the pattern spacing of a patterned film.
[0024] Figure 2 (a) shows a top view of the contact hole pattern template used in the present application under a scanning electron microscope. Figure 2 (b), (c), and (d) respectively show the top views of the contact hole pattern template after the pattern shrinkage is carried out by heating the composition of Example 1 of the present application at 100° C., 120° C., and 150° C., respectively. Figure 2 (e) shows a top view of a scanning electron microscope of the contact hole pattern template after the pattern shrinkage is carried out by heating the composition of Comparative Example 1 at a temperature of 150°C.
[0025] Figure 3 (a) shows a scanning electron microscope top view of the line pattern template used in this application, Figure 3 (b), (c), and (d) respectively show the scanning electron microscope top views of the line pattern template after the pattern shrinkage is carried out by heating the composition of Example 2 of the present application at temperatures of 100°C, 120°C, and 135°C, respectively. DETAILED DESCRIPTION
[0026] The embodiments of the present application will be described below in conjunction with the drawings in the embodiments of the present application.
[0027] In advanced semiconductor manufacturing processes, the patterning process generally includes the following steps: (1) coating a patterning composition (such as a chemically amplified photoresist including a base resin and a photoacid generator) on a substrate to form a patterned material film layer; (2) selectively exposing the patterned material film layer through an exposure source through a mask with a predetermined pattern, causing the photoacid generator in the exposure area to decompose and generate acid; in the baking process after exposure, the photoacid catalyzes the deprotection of the acid-labile protecting groups in the base resin in the exposure area, thereby increasing the polarity of the base resin in the exposure area, thereby producing a difference in the solubility of the developer between the exposure area and the unexposed area; (3) after exposure and baking, the patterned material film layer is developed with a developer, leaving a patterned film having the same or opposite pattern as the mask on the substrate, and the substrate can be selectively etched using the patterned film as a mask. Among them, if the exposed area of the patterned material is removed by the developer (such as an aqueous solution of tetramethylammonium hydroxide) during development, the development can be called "positive development", and the photoresist pattern left on the substrate is a positive pattern, which is basically the same as the pattern of the exposure mask; if the unexposed area of the patterned material is removed by the developer (such as an organic solvent such as n-butyl acetate) during development, the development can be called "negative development", and the photoresist pattern left on the substrate is a negative pattern, which is basically complementary to the pattern of the exposure mask.
[0028] Regardless of whether it is positive development or negative development, the pattern surface of the above-mentioned patterned film left on the substrate has functional groups such as carboxyl and / or hydroxyl groups generated by the deprotection of the acid-labile protective groups (generally, the positive pattern only has these functional groups on the pattern surface, and the negative pattern has these functional groups inside and on the surface), and these functional groups provide reaction sites that can be used by the pattern miniaturization material. Common pattern miniaturization materials usually contain resins and macromolecular crosslinking agents. The pattern miniaturization material is coated on the surface of the above-mentioned patterned film. Under heating conditions, the crosslinking agent in the composition can cause the resin to undergo a crosslinking and curing reaction with the carboxyl and / or hydroxyl groups on the surface of the patterned film, so that the pattern of the patterned film becomes wider. After removing the pattern miniaturization material that has not been crosslinked and cured with the patterned film, a patterned film with a shrunk pattern spacing (such as a reduced line gap, a reduced through-hole size, etc.) is obtained. The resolution of the deposited material pattern (such as metal interconnection lines, trench filling structures) obtained by filling the pattern gap, or the functional layer pattern obtained by etching with it as a mask is greater than the pattern obtained based on the initial patterned film.
[0029] However, the cross-linking reaction between the macromolecular cross-linking agent in the existing graphic miniaturization material and the surface of the patterned film usually causes a large size shrinkage of the patterned film. For the initial patterned film with a high resolution, especially the initial patterned film formed by the patterning process with an exposure wavelength less than or equal to 193 nm, the excessive size shrinkage may cause pattern bridging and reduce the pattern quality. In order to solve this technical problem, the embodiment of the present application provides a composition that can be used as a graphic miniaturization material, and the small molecule coupling agent therein can achieve an appropriate degree of size shrinkage of the patterned film and ensure the uniformity of the graphic size to meet the requirements of high-resolution patterning.
[0030] An embodiment of the present application provides a composition for being arranged on the surface of a patterned film, the composition comprising a resin, a coupling agent and a non-aqueous organic solvent, wherein the coupling agent comprises an organic metal ester coupling agent, and the central metal atom of the organic metal ester coupling agent comprises one or more of titanium (Ti), zirconium (Zr), and aluminum (Al); the structure of the resin comprises a first repeating unit and a second repeating unit, the side chain of the first repeating unit has at least one of a hydroxyl group and a carboxyl group, and the second repeating unit does not contain a hydroxyl group or a carboxyl group; and the molar proportion of the first repeating unit in all the repeating units of the resin is 30%-80%.
[0031] The above composition uses a small molecule organic metal ester coupling agent, which has a central metal atom and multiple organic groups (such as substituted or unsubstituted alkoxy groups). Under heating conditions, the organic groups can achieve chemical bonding between the central metal atom and the hydroxyl or carboxyl group on the first repeating unit in the above resin after a series of changes, and can also achieve chemical bonding between the central metal atom and specific reactive groups (such as carboxyl groups, hydroxyl groups, etc.) on the surface of the patterned film formed by the patterning process. Therefore, with the help of the organic metal ester coupling agent, a stable connection between the resin and the surface of the patterned film is achieved, and a chemical thickening layer of a certain thickness is formed on the surface of the patterned film. After removing the resin and coupling agent not connected to the surface of the patterned film, a patterned film with a moderately increased thickness of the side wall of the pattern and a moderately uniformly reduced pattern spacing can be obtained. Moreover, since the above-mentioned organic metal ester coupling agent is a small molecule substance rather than a high molecular polymer, the thickness of the chemical thickening layer formed by its coupling effect is thinner than the thickness of the thickening layer formed by means of a polymer cross-linking agent, and the shrinkage range of the pattern spacing of the patterned film is relatively small, thereby reducing the probability of pattern defects. The coupling of the organic metal ester coupling agent also shortens the distance between the resin and the surface layer of the patterned film, making the above-mentioned chemical thickening layer denser and more uniform in thickness, thereby effectively improving the uniformity of the shrinkage range of the key dimensions of the patterned film.
[0032] In addition, the molar ratio of the first repeating unit containing hydroxyl and / or carboxyl groups in the above-mentioned resin is controlled to be 30%-80%. In this way, the solubility of the resin in non-aqueous organic solvents will not be reduced due to the molar ratio of the first repeating unit that can react with the coupling agent in the resin being too high, nor will the amount of resin connected to the surface of the patterned film be reduced due to the molar ratio of the first repeating unit being too low, and the patterned film cannot be effectively thickened.
[0033] Therefore, by coating the above-mentioned composition on the surface of the patterned film and undergoing certain treatments, the critical dimensions of the patterned film can be appropriately reduced, and the degree of size reduction is relatively uniform, which can better meet the requirements of high-resolution patterning, and a patterned film with a smaller critical dimension can be produced without replacing new exposure equipment with a shorter wavelength.
[0034] The resin may include a copolymer having both the first repeating unit and the second repeating unit, wherein the first repeating unit accounts for 30-80% by mole of all repeating units in the copolymer. Specifically, the mole ratio may be 35%, 40%, 42%, 45%, 48%, 50%, 52%, 55%, 58%, 60%, 70%, 75% or 78%, etc. In addition, the resin may include one or more copolymers having different structures.
[0035] In some embodiments of the present application, the weight average molecular weight M of the resin is w In the range of 1000-20000. Control the M of the resin that can react with the coupling agent w In an appropriate range, it can be ensured that the number of the first repeating units in the resin that can be chemically bonded with the coupling agent is not too small, which is conducive to ensuring that the composition can effectively thicken the patterned film, and at the same time will not be affected by the M of the resin. w Too large will result in low solubility of the resin in the above composition. w It can be measured by gel permeation chromatography (GPC) using polystyrene as a standard.
[0036] Exemplarily, the M of the resin w 2000, 3000, 4000, 4500, 5000, 5500, 6000, 6500, 7000, 7500, 8000, 8500, 9000, 9500, 10000, 12000, 15000, 18000 or 19000, etc. In some possible embodiments, the weight average molecular weight M of the resin is w In the range of 4000-10000, this is more conducive to the resin having good solubility in non-aqueous organic solvents and having a moderately obvious thickening effect on the patterned film.
[0037] In the embodiment of the present application, the above-mentioned organic metal ester coupling agent may include at least one of titanate, zirconate, aluminate, aluminum zirconate coupling agent, and aluminum-titanium composite coupling agent. Among them, the central metal atoms of titanate, zirconate, and aluminate are Ti, Zr, and Al, respectively. Of course, titanate, zirconate, and aluminate may have one or more metal atoms. The central metal atom of aluminum zirconate includes Al and Zr. The central metal atom of aluminum-titanium composite coupling agent includes Al and Ti.
[0038] In some embodiments of the present application, the above-mentioned organic metal ester coupling agent may include at least one of titanate, zirconate, and aluminate. The present application does not specifically limit the structure of the above-mentioned titanate, zirconate, and aluminate, as long as the coupling effect can be achieved.
[0039] For example, the titanate coupling agent may include tetraethyl titanate (Ti(OCH2CH3)4), tetra-n-propyl titanate (Ti(OCH2CH2CH3)4), tetraisopropyl titanate (structural formula: ), tetrabutyl titanate (Ti(OCH2CH2CH2CH3)4), bis(acetylacetonato) diisopropyl titanate (structural formula is ), diisopropyl di(triethanolamine) titanate (structural formula: )、Hexabutoxy-μ-titanium(IV) oxide (structural formula is ) etc.
[0040] The zirconate coupling agent may include one or more of tetraethyl zirconate, tetra-n-propyl titanate, tetraisopropyl zirconate, tetra-n-butyl zirconate, and the like.
[0041] Among them, the aluminate coupling agent can include triethyl aluminate, triisopropyl aluminate, tributyl aluminate, tribenzyl aluminate, aluminum triacetylacetonate, , bis(acetylacetonato)isopropylaluminate , (acetylacetonato) diisopropylaluminate , (ethyl acetoacetate) diisopropoxyaluminate One or more of the above.
[0042] The following uses zirconate with the chemical formula Zr(OR)4 (-OR is a substituted or unsubstituted alkoxy group) as an example to illustrate the coupling effect of the above-mentioned organic metal ester coupling agent with the resin in the above-mentioned composition or the surface of the patterned film.
[0043] The alkoxy group -OR in Zr(OR)4 is converted into -OH when it meets water (the water may come from the air or the moisture released by the patterned film carrying the above composition under heating conditions). Under heating conditions, Zr-OH can form a chemical bond with -OH in the resin or -OH on the surface of the patterned film through dehydration condensation (such as through -Zr-O-bonding), or Zr-OH can form a chemical bond with -OH in the resin or -COOH on the surface of the patterned film (such as through -Zr-OC(=O)-bonding), so that the central metal atom Zr in the zirconate can be used to achieve chemical bonding with the surface of the patterned film and the resin at the same time. Moreover, since the resin and the surface layer of the patterned film are bridged by chemical bonds containing Zr atoms, the thickness of the above chemical thickening layer is relatively small, uniform and dense, which is conducive to obtaining a high-quality patterned film with moderate and uniform shrinkage of the pattern spacing.
[0044] In addition, for the above-mentioned organic metal ester coupling agents containing acetylacetonate or ethyl acetoacetate in the structure (such as aluminum triacetylacetonate, (ethyl acetoacetate) diisopropoxyaluminate), the acetylacetonate or ethyl acetoacetate can be coordinated with the central metal atom Ti, Zr, Al, etc. Under certain conditions, the acetylacetonate or ethyl acetoacetate can be replaced by -COOH or -OH in the above-mentioned resin or patterned film to achieve connection between the resin and the patterned film surface.
[0045] In some embodiments of the present application, the coupling agent may further include an organosilane having at least three alkoxy groups in its structure. The three alkoxy groups are connected to the same silicon atom. The organosilane is not a polymer and may have one or more silicon atoms in its structure. The alkoxy group may be substituted or unsubstituted. The substituent in the substituted alkoxy group may include at least one of an alkoxy group, an aryl group, etc.
[0046] In some possible embodiments, the organosilane comprises an orthosilicate having a chemical formula of Si(OR)4, wherein each R may be the same or different. Each occurrence of R is independently selected from substituted or unsubstituted C 1-6 Alkyl. The coupling ability of the orthosilicate with 4 -ORs is very strong, and it can be used to connect the resin in the above composition with the surface of the patterned film, which can better meet the needs of establishing a stable chemical thickening layer of appropriate thickness on the surface of the patterned film. Among them, the substituents in the substituted alkyl may include but are not limited to one or more of amine, alkoxy, aryl, etc. An exemplary amine group may be -N(CH2CH2OH). The number of carbon atoms in the alkoxy group may be 1-6, for example, 1, 2, 3, 4, 5 or 6. The aryl group may be, for example, phenyl, or naphthyl. In some possible embodiments, the substituted alkyl may be C 1-4 Alkoxy substituted C 1-6In some embodiments, each R can be independently selected from one or more of methyl, ethyl, n-propyl, isopropyl, n-butyl, 2-methoxyethyl, and benzyl.
[0047] In some other possible embodiments of the present application, the silane may include a silane coupling agent with a chemical formula of Y-Si(OR)3, where R is defined as above, and Y represents an organic functional group. Exemplary Y may include one of an alkyl group, a phenyl group, a vinyl group, a (meth)acryloxy group, an epoxy group, and an amine group.
[0048] The coupling mechanism of the orthosilicate or silane with the chemical formula Y-Si(OR)3 can be found in the introduction of zirconate Zr(OR)4 in the previous text of this application, except that the Zr atom is replaced by Si.
[0049] In some embodiments of the present application, in the above-mentioned composition, the mass of the coupling agent is 1%-30% of the mass of the resin. It can be ensured that the above-mentioned composition has a suitable content of coupling agent to ensure that it can connect a certain amount of resin to the surface of the patterned film to effectively thicken the patterned film without causing material waste of the coupling agent. The mass of the coupling agent here refers to the sum of the mass of the above-mentioned organic metal ester coupling agent and the organosilane (if any). If the above-mentioned composition does not contain organosilane, the mass of the coupling agent here only refers to the total mass of the above-mentioned organic metal ester coupling agent. Specifically, the mass of the coupling agent can be 2%, 5%, 8%, 10%, 12%, 15%, 16%, 12%, 15%, 16%, 18%, 20%, 22%, 25%, or 28% of the mass of the resin. In some embodiments, the mass of the above-mentioned coupling agent can be 10%-25% of the mass of the resin.
[0050] In some embodiments of the present application, in the above-mentioned composition, the total mass proportion of the coupling agent and the resin is 0.5-5wt%. The composition has a suitable solid content, which can ensure that after being coated on the patterned film and heated, the graphic sidewall of the patterned film can be effectively thickened, and the composition will not be wasted due to the limited degree of thickening required for the patterned film. Specifically, in the composition, the total mass proportion of the coupling agent and the resin can be 0.8wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt% or 4.8wt%, etc.
[0051] In the present application, the structures of the first repeating unit and the second repeating unit of the above resin are not particularly limited. In some embodiments of the present application, the first repeating unit includes one or more of a styrene repeating unit having at least one of a hydroxyl group and a carboxyl group on the benzene ring, an acrylate repeating unit having at least one of a hydroxyl group and a carboxyl group on the side chain, and an acrylamide repeating unit having at least one of a hydroxyl group and a carboxyl group on the side chain.
[0052] In some cases, the styrene repeating unit having at least one of a hydroxyl group and a carboxyl group on the benzene ring can be represented by the structure shown in the following (I-1):
[0053] (Ⅰ-1)
[0054] Wherein, R1 is selected from a hydrogen atom (H) or a methyl group (-CH3); and Z contains at least one of -OH and -COOH.
[0055] In some embodiments, Z is -OH, -COOH, or a substituted alkyl group whose substituent includes at least one of -OH and -COOH. Wherein, when Z is the substituted alkyl group, -OH or -COOH is connected to the benzene ring in (I-1) through an alkylene group. The number of carbon atoms of the substituted alkyl group may be 1-6, specifically 1, 2, 3, 4, 5 or 6. In addition, the substituted alkyl group may also have other substituents other than -OH or -COOH, which is not limited in this application. Wherein, the substituted alkyl group may or may not contain a heteroatom linking group, such as one or more of an ether bond (-O-), a thioether bond (-S-), a carbonyl group (-C(=O)-), etc. Exemplarily, Z may be -CH2CH2OH, -CH2CH2COOH, -OCH2CH2OH, etc.
[0056] The acrylic acid ester repeating unit or acrylamide repeating unit having at least one of a hydroxyl group and a carboxyl group on the side chain can be represented by the structure shown in the following (I-2):
[0057] (I-2)
[0058] Wherein, R2 is selected from a hydrogen atom (H) or a methyl group (-CH3); L1 is independently selected from *-COO-, or *-CONH- each time it appears, and the * end is connected to the main chain carbon atom of formula (Ⅰ-2); R3 is independently selected from a substituted alkyl or substituted aryl group including at least one of -OH and -COOH each time it appears.
[0059] Among them, when L1 in formula (Ⅰ-2) is *-COO-, the structure shown in formula (Ⅰ-2) is specifically an acrylic acid ester repeating unit (which can be an acrylic acid alkyl ester repeating unit or an acrylic acid aryl ester repeating unit) having at least one of a hydroxyl group and a carboxyl group in the side chain; when L1 in formula (Ⅰ-2) is *-CONH-, the structure shown in formula (Ⅰ-2) is an acrylamide repeating unit (which can be an aliphatic repeating unit or an aromatic acrylamide repeating unit) having at least one of a hydroxyl group and a carboxyl group in the side chain.
[0060] For R3, -OH or -COOH can be directly connected to a carbon atom in an alkyl or aryl group, or indirectly connected to a carbon atom in an alkyl or aryl group through other groups. For example, the substituent in the substituted alkyl group may specifically include -OH, -COOH, or an aryl group substituted by at least one of -OH and -COOH, and the substituent in the substituted aryl group may specifically include at least one of -OH, -COOH, an alkyl group or an alkoxy group substituted by at least one of -OH and -COOH. Among them, the number of carbon atoms of the substituted alkyl group may be 1-6, and further may be 1-4. The number of carbon atoms in the substituted aryl group may be 6-20, and further 6-10. The number of carbon atoms here may be compared to the unsubstituted alkyl or aryl group. In addition, the substituted alkyl or substituted aryl group may also have other substituents other than -OH or -COOH. Exemplary R3 may be -Ph-OH, -Ph-COOH, -Ph-CH2CH2COOH, -CH2CH2OH, or -CH2CH2-Ph-OH, etc.; Ph represents phenyl.
[0061] In some embodiments of the present application, the second repeating unit includes one or more repeating units derived from styrene-based substances without hydroxyl and carboxyl groups, alkyl acrylates, and alkyl methacrylates. That is, the second repeating unit includes at least one of styrene-based repeating units without hydroxyl and carboxyl groups, alkyl acrylate repeating units, and alkyl methacrylate repeating units.
[0062] For example, the structure of the styrene repeating unit without hydroxyl and carboxyl groups may be as shown in the above formula (I-1), except that Z does not contain -OH or -COOH. For example, the benzene ring may have one or more of hydrogen atoms, halogen atoms, halogenated or unsubstituted alkyl groups, or alkoxy groups. Among them, the structure of the alkyl acrylate repeating unit without hydroxyl and carboxyl groups may be: , the structure of the repeating unit of alkyl methacrylate containing no hydroxyl group and no carboxyl group can be: , each R' is a substituted alkyl group or an unsubstituted alkyl group not containing -OH or -COOH.
[0063] In the embodiment of the present application, the non-aqueous organic solvent in the above-mentioned composition may include one or more of an alcohol solvent and an ether solvent. These solvents are more conducive to the above-mentioned coupling agent and the resin with a reactive group that can act on the coupling agent to be dissolved and stably present therein, and it is not easy to dissolve the patterned film in contact with the composition. Among them, the alcohol solvent includes one or more of methanol, ethanol, n-propanol, isopropanol, n-butanol, sec-butanol, 4-methyl-2-pentanol, etc. The ether solvent may include one or more of n-butyl ether, diisoamyl ether, dipropylene glycol dimethyl ether, etc.
[0064] The present application also provides an application of the above-mentioned composition of the present application in reducing the critical dimension of a pattern.
[0065] The application is specifically to reduce the pattern spacing of the patterned film (specifically the photoresist pattern) during the manufacturing process of the semiconductor device. It can also be said that the composition is specifically used as a pattern shrinking material. With the help of the patterned film with moderately and evenly reduced pattern spacing, a functional layer pattern with smaller critical dimensions and higher resolution can be produced, thereby obtaining a semiconductor device with a higher degree of integration.
[0066] In the semiconductor manufacturing process, the above composition can be used as a pattern shrinking material, which is arranged on the surface of a patterned film formed by a patterning process on a substrate. After heating, a part of the composition material near the interface of the patterned film reacts with the surface of the patterned film to form a chemical thickening layer, thereby increasing the thickness and width of the pattern. After removing the unreacted composition material, a fine patterned film with a smaller and more uniform pattern spacing than the initial patterned film is formed. For details, please refer to the present application Figure 1 A schematic diagram showing the use of the composition of an embodiment of the present application to reduce the pattern spacing of a patterned film.
[0067] Wherein, for a patterned film having a contact hole pattern, the reduction of the critical dimension may refer to the reduction of the hole diameter. For a patterned film having a line pattern, the reduction of the critical dimension may refer to the reduction of the line spacing.
[0068] The embodiment of the present application also provides a method for manufacturing a semiconductor device. The method for manufacturing a semiconductor device may include the following steps S01, S02, and S03.
[0069] Step S01, such as Figure 1 As shown in (a), a substrate 10 having a patterned film 20 on its surface is provided, and the surface of the patterned film 20 has at least one of a hydroxyl group and a carboxyl group.
[0070] In the embodiment of the present application, the patterned film 20 is formed by a patterning process, and the patterning process generally includes steps such as coating a patterned composition, exposing, baking, and developing. The patterned film 20 includes but is not limited to being formed by patterning techniques such as ArF lithography. The resolution of the patterned film 20 formed by these patterning techniques is already high, and it is more meaningful to perform graphic miniaturization on it. A patterned film with a smaller critical dimension can be obtained at a lower cost without replacing expensive new exposure equipment. Optionally, the thickness of the patterned film 20 formed by these patterning techniques is in the range of 20nm-200nm. This can ensure that the graphics have a suitable aspect ratio and are not prone to collapse.
[0071] In some embodiments of the present application, the patterned film 20 may be a photoresist pattern, and may further be a chemically amplified photoresist pattern. The chemically amplified photoresist may include a base resin and a photoacid generator. Since the patterned film 20 is a film having a certain pattern formed by a patterning process (that is, the chemically amplified photoresist has been exposed and developed, and the acid-labile groups have been deprotected in the exposed area), the surface of the patterned film 20 may have carboxyl groups (-COOH) or hydroxyl groups (-OH), with carboxyl groups being the majority. In addition, in some cases, the surface of the patterned film 20 may also have hydroxyl groups derived from other repeating units in the base resin other than the acid-labile repeating units.
[0072] The substrate 10 can be selected according to specific needs, for example, it can be a silicon wafer, or a silicon wafer covered by other coatings. The coatings can include one or more of an anti-reflective coating, an epitaxial layer, a metal layer, a dielectric layer (such as SiO2, or Si3N4), etc.
[0073] Step S02, such as Figure 1 As shown in (b), the composition of the embodiment of the present application is coated on the surface of the patterned film 20 to form a film material 30, and then heated to allow the film material 30 to react with the contact portion of the patterned film 20.
[0074] Wherein, the coating method includes but is not limited to spin coating, dip coating, brush coating, etc. In the above coating process, the above composition is not only located on the surface of the patterned film 20, but also located in the pattern gap of the patterned film 20. Wherein, the thickness of the film material 30 is preferably to fill the pattern gap (including pores) of the patterned film 20 and thicken by 10-30%. This is conducive to ensuring the formation of a chemical thickening layer of appropriate thickness, while not affecting the convenient removal of unreacted composition materials. Wherein, the coating thickness of the film material 30 can be adjusted according to the amount of solvent added to the composition. Generally, the higher the solid content of the above composition, the thicker the thickness of the film material 30 formed by coating. Optionally, the solid content in the above composition is 0.5-5wt%. So that the graphic sidewalls of the patterned film 20 can be effectively thickened without causing material waste.
[0075] In step S02, the heating may be heating the substrate 10 with the patterned film 20 and the film material 30. During the heating process, a reaction occurs between the patterned film 20 and the film material 30 at the contact interface. Figure 1 As shown in (c), a chemical thickening layer 40 of a certain thickness is formed on the surface of the patterned film 20. The chemical thickening layer 40 is mainly formed by chemically bridging the resin in the film material 30 and the surface of the patterned film 20 with the help of the small molecule coupling agent in the above-mentioned film material 30 under heating conditions. For the formation mechanism of the chemical thickening layer 40, please refer to the explanation in the previous text of this application.
[0076] In the embodiment of the present application, the heating temperature may be 100-180°C, for example, 110°C, 120°C, 130°C, 150°C, 160°C, or 170°C. The heating time may be 30 seconds to 180 seconds, for example, 45s, 60s, 90s, 120s, etc. Controlling the heating temperature may control the reaction rate of the coupling agent in the film material 30 with the surface active groups of the patterned film 20 and the resin in the film material 30, thereby controlling the thickness of the chemical thickening layer 40 and the shrinkage of the pattern. Controlling the heating time may also control the thickness of the chemical thickening layer 40.
[0077] Step S03, after removing the unreacted film material 30 with a cleaning solution, a fine patterned film 20' with reduced pattern spacing is obtained on the substrate 10, such as Figure 1 As shown in (d).
[0078] The above-mentioned "unreacted film material 30" specifically refers to the film material 30 that is not grafted to the surface of the patterned film 20. This part of the film material can be washed away by the cleaning solution, while the part of the film material grafted to the surface of the patterned film 20 (i.e., the chemical thickening layer 40) can be retained without being washed away by the cleaning solution. Among them, the fine patterned film 20' can include the initial patterned film 20 and the chemical thickening layer 40 connected thereto. The presence of the chemical thickening layer 40 increases the thickness and pattern width of the fine patterned film 20', so that the interval between adjacent patterns of the fine patterned film 20' becomes smaller.
[0079] In the embodiment of the present application, the cleaning liquid may include an alkaline aqueous solution or an organic solvent. The cleaning liquid may be applied to the substrate 10 by spin coating, spraying, dipping, etc. Among them, the alkali in the alkaline aqueous solution may include one or more of tetramethylammonium hydroxide (TMAH), tetraethylammonium hydroxide (TEAH), tetrapropylammonium hydroxide (TPAH), tetrabutylammonium hydroxide (TBAH), etc. The organic solvent may include, but is not limited to, one or more of alcohol solvents (such as ethanol, isopropanol, ethylene glycol, propylene glycol, 1-pentanol, 4-methyl-2-pentanol, etc.), ester solvents (such as n-butyl acetate, propylene glycol monomethyl ether acetate, ethyl acetate, ethyl lactate, butyrolactone, etc.), ether solvents (such as propylene glycol monomethyl ether, propylene glycol ethyl ether, n-butyl ether, diisoamyl ether, dipropylene glycol dimethyl ether, anisole, etc.). The patterned film 20 formed by the patterning process has strong tolerance to these cleaning liquids, and when they are used to remove the unreacted film material 30, the patterned film 20 below will not be damaged.
[0080] Optionally, the pattern pitch of the fine patterned film 20' in step S03 is reduced by 3-15 nm compared to the pattern pitch of the patterned film 20 in step S01. Figure 1 That is, Δd' is 3-15nm smaller than Δd. That is, the composition provided in the present application can reduce the pattern spacing of the patterned film 20 by 3-15nm. For the patterned film 20 with a higher pattern resolution, the composition provided in the present application can appropriately shrink the pattern spacing of the patterned film 20, and adjacent patterns will not stick together.
[0081] After the above step S03, a fine patterned film 20' is formed on the substrate 10. The narrower pattern spacing of the fine patterned film 20' can be used to define smaller features than when only the patterned film 20 is used. In some embodiments, the pattern of the fine patterned film 20' can be transferred to the substrate to obtain a patterned substrate. The patterned substrate can be used in the manufacture of semiconductor devices such as chips to improve the manufacturing accuracy and quality of the devices.
[0082] After the above step S03, other functional layers can be prepared. For example, after the above step S03, a metal material can be deposited in the gap to form a metal pattern layer. The fine patterned film 20' with a narrower gap can also be used as a mask to perform high-precision etching on the substrate 10, and the pattern thereon can be transferred to the substrate 10 by etching to further realize the preparation of other coatings.
[0083] The manufacturing method of the above-mentioned semiconductor device provided in the embodiment of the present application, by adopting the composition of the embodiment of the present application as the pattern shrinkage material, can achieve a moderate and uniform reduction in the pattern spacing distance of the formed patterned film, obtain a fine pattern with a smaller critical dimension at a lower cost, and ensure that the obtained pattern has high clarity and small defects, which is conducive to the high-integration and high-precision development of semiconductor processes.
[0084] The embodiment of the present application also provides a semiconductor device, which is manufactured by the semiconductor manufacturing method of the embodiment of the present application. The manufacturing precision of the semiconductor device is high.
[0085] The semiconductor device may include but is not limited to a chip, etc. It is understandable that the semiconductor device product usually does not contain the fine patterned film 20'.
[0086] The embodiments of the present application are further described below with reference to a plurality of embodiments.
[0087] Example 1
[0088] (I) Preparation of resin:
[0089] 8.00 g of N-p-hydroxyphenyl acrylamide, 4.94 g of 4-tert-butoxystyrene and 2.42 g of initiator dimethyl azobisisobutyrate were dissolved in 46 g of isopropanol solvent, and the oxygen in the system was removed by three freeze-thaw cycles, and then reacted at a reflux temperature of 83°C for 6 hours. The obtained reactant was vacuum dried to remove the solvent, 46 g of ethyl acetate was added and stirred to dissolve, and then 5 times the volume of n-heptane was added for precipitation. After suction filtration, the precipitation operation was repeated once, and the solid was collected. The obtained solid was vacuum dried at 60°C to obtain a weight average molecular weight M w The resin P1 has a molecular weight of 5808 and a molecular weight distribution index PDI of 2.45.
[0090] The preparation process of resin P1 is as follows:
[0091]
[0092] From the hydrogen nuclear magnetic resonance spectrum of the resin P1, it was found that the molar ratio of the repeating unit derived from N-p-hydroxyphenylacrylamide to the repeating unit derived from 4-tert-butoxystyrene (ie, m:n) was 3:2.
[0093] (II) Preparation of the composition:
[0094] 2.6 g of resin P1 was dissolved in 97 g of n-butanol, and 0.4 g of tetraisopropyl titanate was added to the resulting solution. After sufficient stirring to dissolve, the solution was filtered through a polytetrafluoroethylene filter with a pore size of 0.22 μm to obtain a composite solution, which was recorded as F1.
[0095] (III) Preparation of pattern template 1:
[0096] The bottom anti-reflective coating material is coated on a silicon wafer substrate and heated on a hot plate at 205°C for 60 seconds to form a 30nm thick bottom anti-reflective coating. Then, a chemically amplified photoresist is coated on the bottom anti-reflective coating and heated on a hot plate at 110°C for 60 seconds to form a 120nm thick photoresist film layer. The photoresist film layer is exposed through a mask using an ArF exposure device, and baked on a hot plate at 95°C for 60 seconds after exposure. Thereafter, an aqueous solution of tetramethylammonium hydroxide with a concentration of 2.38wt% is used for immersion development for 60 seconds to remove the exposed portion, and then washed with deionized water for 10 seconds to form a hexagonally arranged contact hole pattern template P-CH (which can be referred to as pattern template 1) with a pore size of 130.44nm and a pore spacing of 345nm. The scanning electron microscope top view is shown as follows Figure 2 As shown in (a).
[0097] (iv) Compositions for graphic miniatures:
[0098] The composition F1 is spin-coated onto the contact hole pattern template P-CH at a speed of 1500 rpm to form a film material, and heated on hot plates at 100°C, 120°C, and 150°C for 60 seconds, respectively, to react with the portion of the film material in contact with the surface of the pattern template. Then, it is immersed in a tetramethylammonium hydroxide aqueous solution with a concentration of 2.38wt% for 30 seconds to remove the film material that is not connected to the surface of the graphic film, and washed in water for 10 seconds to obtain a contact hole pattern after the aperture is shrunk. The top views of the contact hole pattern after the aperture is shrunk obtained by heating at 100°C, 120°C, and 150°C are shown in FIG. Figure 2 The average pore size, pore size standard deviation, and pore size shrinkage of the contact hole patterns were measured from these figures, and the results are summarized in Table 1 below.
[0099] Comparative Example 1
[0100] Preparation of the composition: 2.6 g of resin P1 was dissolved in 97 g of n-butanol, and 0.4 g of a commercial crosslinking agent (methylated hexahydroxymethyl melamine resin) was added. After sufficient stirring to dissolve, the mixture was filtered through a polytetrafluoroethylene filter with a pore size of 0.22 μm to obtain a composition solution.
[0101] The composition provided in Comparative Example 1 was coated on the contact hole pattern template PCH, and heated on a hot plate at 150° C. for 60 seconds, then immersed in a 2.38 wt % tetramethylammonium hydroxide aqueous solution for 30 seconds to remove materials not connected to the surface of the contact hole pattern template, and then washed in water for 10 seconds to obtain a top view of the contact hole pattern with a shrunken aperture under a scanning electron microscope as shown in FIG. Figure 2 The average pore size, pore size standard deviation and pore size shrinkage of the contact hole pattern were measured, and the results are also shown in Table 1 below.
[0102] Table 1
[0103]
[0104] Note: The aperture shrinkage refers to the difference between the average aperture of the contact hole obtained after the composition undergoes pattern shrinkage and the average aperture in the initial contact hole pattern template.
[0105] It can be seen from Table 1 that after the contact hole pattern template was subjected to pattern shrinkage using the composition F1 of Example 1 at heating temperatures of 100°C, 120°C, and 150°C, the average pore size shrinkage of the contact holes was 11.48nm, 6.16nm, and 3.85nm, respectively, which is much smaller than the pore size shrinkage caused by the composition of Comparative Example 1 using a polymer resin as a cross-linking agent, greatly reducing the probability of deformation of the contact hole shape. In addition, the pore size standard deviation of the contact holes in the contact hole pattern obtained by using the composition of Example 1 is also lower than that of Comparative Example 1, which can indicate that the pore size uniformity is also improved.
[0106] Example 2
[0107] (I) Preparation of resin:
[0108] 8.00 g of hydroquinone monomethacrylate, 4.87 g of 4-tert-butoxystyrene and 2.23 g of dimethyl azobisisobutyrate were dissolved in 46 g of isopropanol solvent, and the oxygen in the system was removed by three freeze-thaw cycles, and then the reaction was carried out at a reflux temperature of 83 ° C for 6 hours. After the obtained reactant was vacuum dried to remove the solvent, 46 g of ethyl acetate was added and stirred to dissolve, and then 5 times the volume of n-heptane was added for precipitation. After suction filtration, the precipitation operation was repeated once, and the solid was collected. The obtained solid was vacuum dried at 60 ° C to obtain a weight average molecular weight M wThe resin P2 has a molecular weight of 7025 and a molecular weight distribution index PDI of 2.25. According to the nuclear magnetic resonance test, the molar ratio of the repeating unit derived from hydroquinone monomethacrylate to the repeating unit derived from 4-tert-butoxystyrene in the resin P2 is 3:2.
[0109] The preparation process of resin P2 is as follows:
[0110]
[0111] (II) Preparation of the composition:
[0112] 2.6 g of resin P2 was dissolved in 97 g of n-butanol, and 0.4 g of tetraisopropyl titanate was added to the resulting solution. After sufficient stirring to dissolve, the solution was filtered through a polytetrafluoroethylene filter with a pore size of 0.22 μm to obtain a composite solution, which was recorded as F2.
[0113] (III) Preparation of pattern template 2:
[0114] The bottom anti-reflective coating material is coated on a silicon wafer substrate and heated on a hot plate at 205°C for 60 seconds to form a 30nm thick bottom anti-reflective coating. Then, a chemically amplified photoresist is coated on the bottom anti-reflective coating and heated on a hot plate at 90°C for 60 seconds to form a 90nm thick photoresist film layer. The photoresist film layer is exposed through a mask using an ArF exposure device, and baked on a hot plate at 95°C for 60 seconds after exposure. After that, it is immersed in n-butyl acetate for 30 seconds to remove the exposed part, and washed with deionized water for 10 seconds to obtain a line pattern template N-LS (referred to as pattern template 2) with a line width of 54.66nm and a spacing of 125nm. The scanning electron microscope top view of the line pattern template is shown as follows. Figure 3 As shown in (a).
[0115] (iv) Compositions for graphic miniatures:
[0116] The composition F2 was spin-coated onto the line pattern template N-LS at a speed of 1500 rpm to form a film material, and heated on hot plates at 100°C, 120°C, and 135°C for 60 seconds, respectively, to react with the portion of the film material in contact with the surface of the pattern template. Then, the film material was immersed in ethanol for 30 seconds to remove the film material not connected to the surface of the graphic film, thereby obtaining a line pattern with a shrunk line pitch. The top views of the line pattern with a shrunk line pitch obtained by heating at 100°C, 120°C, and 135°C are shown in the following figures. Figure 3 The line width and line spacing shrinkage of the pattern were measured from these figures, and the results are summarized in Table 2 below.
[0117] Table 2
[0118]
[0119] It can be seen from Table 2 that after the line pattern template was subjected to graphic shrinkage at heating temperatures of 100°C, 120°C and 135°C using composition F2 of Example 2, the graphic line width was appropriately increased and the line spacing was appropriately shrunk accordingly, with the line spacing shrinkage amounts being 6.66nm, 6.01nm and 7.66nm, respectively.
[0120] Example 3
[0121] A composition, which is different from the composition F1 in Example 1 in that 0.4 g of tetraisopropyl titanate is replaced by 0.4 g of tetrabutyl zirconate.
[0122] Example 4
[0123] A composition, which is different from the composition F1 in Example 1 in that 0.4 g of tetraisopropyl titanate is replaced by 0.4 g of (ethyl acetoacetate) diisopropoxyaluminate.
[0124] Example 5
[0125] A composition, which is different from the composition F1 in Example 1 in that 0.4 g of tetraisopropyl titanate in Example 1 is replaced by 0.2 g of isopropyl titanate and 0.2 g of tetraethyl orthosilicate.
[0126] Referring to the method described in the above-mentioned Example 1, the compositions provided in Examples 3-5 were respectively coated on the contact hole pattern template PCH and heated on a hot plate at 120°C for 60 seconds, and then immersed in a 2.38wt% tetramethylammonium hydroxide aqueous solution for 30 seconds to remove the composition material not connected to the surface of the pattern template, and then rinsed in water for 10 seconds to obtain a contact hole pattern with pore size shrinkage, and the average pore size, pore size standard deviation and pore size shrinkage amount were measured. The results are summarized in the following Table 3.
[0127] Table 3
[0128]
[0129] It can be seen from Table 3 that the composition of Example 3 using tetrabutyl zirconate as a coupling agent, the composition of Example 4 using (ethyl acetoacetate) diisopropoxyaluminate as a coupling agent, or the composition of Example 5 using both isopropyl titanate and orthosilicate as coupling agents can also play a role in appropriately shrinking the pore size of the contact hole pattern. The shrinkage amount is about 6nm, which is much smaller than the pore size shrinkage caused by the composition of Comparative Example 1 using a polymer resin as a cross-linking agent, and the pore size uniformity of the shrunk contact holes is also high (reflected by a lower pore size standard deviation).
[0130] Example 6
[0131] Preparation of the composition: 2.8 g of resin P1 was dissolved in 97 g of n-butanol, and 0.2 g of tetraisopropyl titanate was added. After sufficient stirring and dissolution, the mixture was filtered through a polytetrafluoroethylene filter with a pore size of 0.22 μm to obtain a composition. In the composition of Example 6, the mass of the coupling agent was 7% of the mass of the resin.
[0132] Example 7
[0133] Preparation of the composition: 2.4 g of resin P1 was dissolved in 97 g of n-butanol, and 0.6 g of tetraisopropyl titanate was added. After sufficient stirring and dissolution, the mixture was filtered through a polytetrafluoroethylene filter with a pore size of 0.22 μm to obtain a composition. In the composition of Example 6, the mass of the coupling agent was 25% of the mass of the resin.
[0134] Example 8
[0135] A composition, which differs from the composition F1 of Example 1 in that the amounts of monomers used in preparing the resin are changed so that in the obtained resin, the molar ratio of repeating units derived from N-p-hydroxyphenylacrylamide to repeating units derived from 4-tert-butoxystyrene is 3:7.
[0136] Example 9
[0137] A composition, which differs from the composition F1 of Example 1 in that the amounts of monomers used in preparing the resin are changed so that in the obtained resin, the molar ratio of repeating units derived from N-p-hydroxyphenylacrylamide to repeating units derived from 4-tert-butoxystyrene is 8:2.
[0138] Referring to the method described in the above-mentioned Example 1, the compositions provided in Examples 6-9 were respectively coated on the contact hole pattern template PCH and heated on a hot plate at 120°C for 60 seconds, and then immersed in a 2.38wt% tetramethylammonium hydroxide aqueous solution for 30 seconds to remove the composition material not connected to the surface of the pattern template, and then rinsed in water for 10 seconds to obtain a contact hole pattern with pore size shrinkage, and the average pore size, pore size standard deviation and pore size shrinkage amount were measured. The results are summarized in the following Table 4.
[0139] Table 4
[0140]
[0141] From the comparison between Examples 6, 7, and 1 in Table 4, it can be seen that when the solid content of the composition remains unchanged, changing the relative content of the coupling agent and the resin can achieve the regulation of the shrinkage of the pore size in the contact hole pattern. From the comparison between Examples 8, 9, and 1 in Table 4, it can be seen that when the solid content and the coupling agent in the composition remain unchanged, changing the molar ratio of the active repeating unit of the resin in the composition of the embodiment of the present application within a certain range can also achieve the effect of appropriately and uniformly shrinking the pore size in the contact hole pattern.
[0142] The above only expresses the exemplary embodiments of the present application, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present application. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present application, which all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be based on the attached claims.
[0143] It should be understood that the first, second and various numerical numbers involved in this document are only used for the convenience of description and are not used to limit the scope of this application. In this application, "and / or" describes the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone, where A and B can be singular or plural. The character " / " generally indicates that the associated objects before and after are in an "or" relationship.
[0144] In the description of this application, unless otherwise specified, the meaning of "multiple" refers to greater than or equal to two. "At least one" refers to one or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.
[0145] In addition, the numerical range represented by "-" in this application refers to the range that includes the numerical values recorded before and after "-" as the minimum and maximum values, respectively. In this application, expressions about parameter ranges, such as "greater than or equal to (≥)", "less than or equal to (≤)", "above...", and "below..." all include the number itself. The numerical values and numerical ranges involved in the embodiments of this application are approximate values. Due to the influence of manufacturing processes / testing methods, etc., there may be a certain range of errors, which can be considered negligible by those skilled in the art.
Claims
1. A composition for being arranged on the surface of a patterned film to reduce the critical dimension of the pattern, characterized in that: The composition comprises a resin, a coupling agent and a non-aqueous organic solvent, wherein the coupling agent comprises an organic metal ester coupling agent, and the central metal atom of the organic metal ester coupling agent comprises one or more of titanium, zirconium and aluminum; the structure of the resin comprises a first repeating unit and a second repeating unit, the first repeating unit comprises one or more of a styrene repeating unit having at least one of a hydroxyl group and a carboxyl group on a benzene ring, an acrylate repeating unit having at least one of a hydroxyl group and a carboxyl group on a side chain, and an acrylamide repeating unit having at least one of a hydroxyl group and a carboxyl group on a side chain, the second repeating unit does not contain a hydroxyl group or a carboxyl group, and the first repeating unit accounts for 30% to 80% by mole of all repeating units of the resin.
2. The composition according to claim 1, characterized in that The weight average molecular weight of the resin is in the range of 1,000-20,000.
3. The composition according to claim 1, characterized in that The organic metal ester coupling agent includes at least one of titanate, zirconate, and aluminate; wherein the titanate includes one or more of tetraethyl titanate, tetra-n-propyl titanate, tetraisopropyl titanate, tetra-n-butyl titanate, bis(acetylacetonate) diisopropyl titanate, di(triethanolamine) diisopropyl titanate, and hexabutoxy-μ-titanium (IV) oxide; the zirconate includes one or more of tetraethyl zirconate, tetra-n-propyl zirconate, tetraisopropyl zirconate, and tetra-n-butyl zirconate; the aluminate includes one or more of triethyl aluminate, triisopropyl aluminate, tributyl aluminate, tribenzyl aluminate, aluminum triacetylacetonate, bis(acetylacetonate) isopropyl aluminate, (acetylacetonate) diisopropyl aluminate, and (ethyl acetylacetonate) diisopropoxy aluminate.
4. The composition according to any one of claims 1 to 3, characterized in that The coupling agent also includes a silane having at least 3 alkoxy groups in the structure.
5. The composition according to claim 4, characterized in that The silane comprises an orthosilicate of formula Si(OR)4, wherein each R is independently selected from substituted or unsubstituted C 1-6 alkyl.
6. The composition according to claim 1, characterized in that The mass of the coupling agent is 1%-30% of the mass of the resin.
7. The composition according to claim 1, characterized in that In the composition, the total weight ratio of the coupling agent and the resin is 0.5-5wt%.
8. The composition according to claim 1, characterized in that The second repeating unit includes one or more repeating units derived from styrene-based substances without hydroxyl groups and carboxyl groups, alkyl acrylates, and alkyl methacrylates.
9. The composition according to claim 1, characterized in that The non-aqueous organic solvent includes one or more of an alcohol solvent and an ether solvent.
10. The composition according to claim 9, characterized in that The alcohol solvent includes one or more of methanol, ethanol, n-propanol, isopropanol, n-butanol, sec-butanol, and 4-methyl-2-pentanol; the ether solvent includes one or more of n-butyl ether, diisoamyl ether, and dipropylene glycol dimethyl ether.
11. Use of the composition according to any one of claims 1 to 10 in reducing the critical dimension of a pattern.
12. A method for manufacturing a semiconductor device, characterized in that: include: (1) Providing a substrate having a patterned thin film; The surface of the patterned film has at least one of a hydroxyl group and a carboxyl group; (2) applying the composition according to any one of claims 1 to 10 to the surface of the patterned film to form a film material, and performing a heating treatment to react the portion of the film material in contact with the patterned film; (3) Using a cleaning solution to remove the unreacted film material, a fine patterned film with reduced pattern spacing is obtained on the substrate.
13. The manufacturing method according to claim 12, characterized in that: The pattern spacing of the fine patterned film in step (3) is reduced by 3-15 nm compared with the patterned film in step (1).
14. A semiconductor device, characterized in that: The invention is prepared by the manufacturing method according to any one of claims 12 to 13.
Citation Information
Patent Citations
Adhesive coating material
US4533701A